A strategy for transmission network expansion planning considering multiple generation scenarios - Freitas, Patrícia F. S. (2019)
Transmission network expansion planning (TNEP) is subject to several constraints that are driven by new market rules, such as generation uncertainty, demand growth, seasonal climate changes and technological advances. When considering multiple generation scenarios, due to different operational conditions, it is necessary to find an expansion plan that allows the expanded system to operate properly for each scenario. This paper presents a strategy that provides several expansion plans that operate efficiently in all the previously defined generation scenarios and that keep reasonable values for the expansion costs. Thus, the developed mathematical model allows us to find adequate expansion plans with expansion costs that can be controlled, with small infeasibilities in the operation of the system that may not be significant in the long-term planning. The proposed approach is applied to the 24-bus system and the Colombian 93-bus system. The results indicate that the plans obtained using the proposed strategy present much lower expansion costs compared to the conventional TNEP model with multiple generation scenarios, with very low infeasibilities in the operation of the system, which can be corrected in the short-term expansion planning.